At home in postwar France: modern mass housing and the right to comfort (Berghahn monographs in French studies; volume 14) - Rudolph, Nicole C (Berghahn monographs in French studies, 2015)
After World War II, France embarked on a project of modernization, which included the development of the modern mass home.At Home in Postwar Franceexamines key groups of actors - state officials, architects, sociologists and tastemakers - arguing that modernizers looked to the home as a site for social engineering and nation-building; designers and advocates of the modern home contributed to the democratization of French society; and the French home of theTrente Glorieuses, as it was built and inhabited, was a hybrid product of architects', planners', and residents' understandings of modernity. This volume identifies the "right to comfort" as an invention of the postwar period and suggests that the modern mass home played a vital role in shaping new expectations for well-being and happiness.